Physiological responses of piau (Leporinus friderici, Bloch 1794) to transportation - Serra, Monica [UNESP]; Bejo Wolkers, Carla Patricia [UNESP]; Hoshiba, Marcio Aquio; Urbinati, Elisabeth Criscuolo [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2011)
This study evaluated stress indicators of juvenile piau (Leporinus friderici) during and after a 4-hour transportation in order to establish an appropriate transportation protocol for this type of fish. Fish were transported in plastic bags (133.1 g/L) and sampled before loading, during 1, 2, 3 and 4 h and after transportation (2, 6, 12 and 24 h). Blood samples were analyzed for cortisol and glucose levels, hematocrit, hemoglobin level, number and mean corpuscular volume of erythrocytes. Water pH, dissolved oxygen, temperature and ammonia were monitored before, during and after transportation. No mortality was observed through the experiment. Ammonia levels increased throughout transportation, but the low pH values kept NH3 in safe levels for fish. Cortisol levels increased within 4 h of transportation, and returned to control condition 2 h after arrival. Plasma glucose increased within one hour of transportation, reaching peak value within 4 h and returning to initial condition 2 h after arrival. Erythrocyte number and hemoglobin levels showed the lowest levels 2 h after arrival, and mean corpuscular volume increased during transportation, decreasing at 12 and 24 h after arrival. Transporting piau is stressful, but fish recover the initial condition in short time, showing tolerance to the changes in the water quality parameters.
Keywords: Cortisol; Fish transport; Stress